2020
DOI: 10.1002/bies.201900256
|View full text |Cite
|
Sign up to set email alerts
|

KCTD10 Biology: An Adaptor for the Ubiquitin E3 Complex Meets Multiple Substrates

Abstract: Protein ubiquitination constitutes a post‐translational modification mediated by ubiquitin ligases whereby ubiquitinated substrates are degraded through the proteasomal or lysosomal pathways, or acquire novel molecular functions according to their “ubiquitin codes.” Dysfunction of the ubiquitination process in cells causes various diseases such as cancers along with neurodegenerative, auto‐immune/inflammatory, and metabolic diseases. KCTD10 functions as a substrate recognition receptor for cullin‐3 (CUL3), a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In such complexes, a substrate recognition receptor, specifically a BTB domain-containing protein (BTBP), recruits substrates leading to their ubiquitination ( Petroski & Deshaies, 2005 ). One BTBP, KCTD10, recognizes various substrates (e.g., RhoB, CEP97, EIF3D, TRIF, and EPS8) ( Kovačević et al, 2018 ; Nagai et al, 2018 ; Maekawa et al, 2019 ; Murakami et al, 2019 ; Wu et al, 2019 ; Maekawa & Higashiyama, 2020 ; Rodríguez-Pérez et al, 2021 ). We previously reported that the constitutive degradation of an endosomal small GTPase RhoB by the CUL3/KCTD10 E3 complex functions in EGF-induced Rac1 activation specifically in HER2-positive breast cancer cell lines, among other breast cancer subtypes ( Murakami et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In such complexes, a substrate recognition receptor, specifically a BTB domain-containing protein (BTBP), recruits substrates leading to their ubiquitination ( Petroski & Deshaies, 2005 ). One BTBP, KCTD10, recognizes various substrates (e.g., RhoB, CEP97, EIF3D, TRIF, and EPS8) ( Kovačević et al, 2018 ; Nagai et al, 2018 ; Maekawa et al, 2019 ; Murakami et al, 2019 ; Wu et al, 2019 ; Maekawa & Higashiyama, 2020 ; Rodríguez-Pérez et al, 2021 ). We previously reported that the constitutive degradation of an endosomal small GTPase RhoB by the CUL3/KCTD10 E3 complex functions in EGF-induced Rac1 activation specifically in HER2-positive breast cancer cell lines, among other breast cancer subtypes ( Murakami et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 D ), indicating that the first 43 amino acids of SLC7A11 mediate KCTD10 binding. We then defined the KCTD10 binding domain on SLC7A11 by constructing two mutants: a BTB delete mutant (KCTD10ΔBTB) which fails to binds to Cul-3 and a C-terminal delete mutant (KCTD10ΔC), which fails to bind to substrate ( 23 , 24 ) ( SI Appendix , Fig. S2 B ).…”
Section: Resultsmentioning
confidence: 99%
“…Our conclusion is supported by the following lines of evidence: 1) pharmacological inhibition of neddylation or siRNA-based knockdown of Cul-3 causes SLC7A11 accumulation; 2) KCTD10 binds to SLC7A11 via its C-terminal region and SLC7A11 interacts with KCTD10 via its N-terminal domain; 3) KCTD10 overexpression or knockdown decreases or increases SLC7A11 levels, respectively; 4) KCTD10 overexpression or knockdown shortens or extends SLC7A11 protein half-life, respectively; 5) KCTD10 promotes SLC7A11 ubiquitylation for proteasome degradation. Thus, our study adds SLC7A11 to the repertoire of the growing list of KCTD10 substrates ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Humans possess eight CUL proteins, CUL1, CUL2, CUL3, CUL4A, CUL4B, CUL5, CUL7, and CUL9 [11]. The CUL3/RING ubiquitin E3 complex consists of CUL3, substrate recognizing receptors (Bric-à-brac/Tramtrack/Broad complex domain-containing proteins (BTBPs), E2, and E3s (RBX1, ARIH1, DCNLs) [12,13]. BTBPs recognize their substrate proteins and interact with the N-terminus of CUL3, leading to their ubiquitination [14].…”
Section: Introductionmentioning
confidence: 99%